2017
DOI: 10.1080/20477724.2017.1345366
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of brucellosis among veterinary health care professionals

Abstract: The study describes prevalence, clinical symptoms and risk factors for brucellosis in personnel engaged in veterinary health care in Karnataka, India. A total of 1050 sera samples were collected from animal handlers, veterinarians, veterinary students, para-veterinarians and persons engaged in artificial insemination of animals. The sera samples were tested for brucellosis by Rose Bengal plate test (RBPT), serum agglutination test (SAT), IgG and IgM indirect ELISA and PCR. Age, sex, clinical symptoms and risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 29 publications
3
33
4
Order By: Relevance
“…Thus a seroprevalence of 11.5% was found in Andhra Pradesh and 6.5% in Orissa. [21][22] In South and North Karnataka, 2.14%, 0.92% seropositivity was observed respectively among patients with or without fever and those presenting other symptoms for brucellosis 17 . Mangalgi et al 27 conducted a seroepidemiological survey in three districts of Karnataka viz., Bijapur, Bagalkot, and Gulbarga.…”
Section: Seroprevalence Of Brucellosis Among Febrile Patients (Puo)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus a seroprevalence of 11.5% was found in Andhra Pradesh and 6.5% in Orissa. [21][22] In South and North Karnataka, 2.14%, 0.92% seropositivity was observed respectively among patients with or without fever and those presenting other symptoms for brucellosis 17 . Mangalgi et al 27 conducted a seroepidemiological survey in three districts of Karnataka viz., Bijapur, Bagalkot, and Gulbarga.…”
Section: Seroprevalence Of Brucellosis Among Febrile Patients (Puo)mentioning
confidence: 99%
“…In Central Kerala, the overall seroprevalence is about 1.6% which comprises of general population and veterinary students with 2.45% and 1.14% seropositivity respectively 7 . Recently, Shome et al 17 from Karnataka reported overall prevalence of 7.04% among veterinary health care professionals. In our study 8.00% animal handlers were seropositive for brucellosis.…”
Section: Seroprevalence Of Brucellosis Among Animal Handlersmentioning
confidence: 99%
“…Infectious diseases of the liver are other examples of the wide spectrum of non-genetic rare diseases as well as rare manifestations of common diseases. Infections such as brucellosis [29][30][31][32][33] or leishmaniosis 34 are rare in Europe -so is schistosomiasis, which on a world-wide scale is one of the most common infectious diseases and one of the most common liver diseases we know. Furthermore, hepatitis E infection appears to be very common in Europe, with a seroprevalence for anti-HEV antibodies estimated to be around 10-20%.…”
Section: How Common Is Rare?mentioning
confidence: 99%
“…The overall prevalence of brucella antibodies in blood from all collected human samples were 24 / 280 (8.6%), as shown in (Table 1), which is approach or slightly lower percentage with [31] in Pakistan whom found that the prevalence of Brucella infection was (9.33%) according to RBT, while [32] in Egypt reported that the prevalence of Brucella infection was (11.1%) according to RBT. In the study designed by [33] in Karnataka, India noticed that the prevalence of brucellosis by Rose Bengal plate test (RBPT) was 6.38 %. In Angola, namibe province, [22] mentioned that the general weighted prevalence of brucellosis was 15.6% from a population of 131 workers of butchers, slaughter rooms, slaughterhouse, and 192 breeders sampled randomly.Also,table1shows that the female are more exposed to infection with Brucella, the rate of infection in female was 13/ 134 (9.7%), compared with the rate of infection in males were 11/146 ( 7.5%).This result was compatible with [34] in Pakistan, who indicated that the prevalence of brucellosis in females (25.58%), while in males (10.18%).…”
Section: Prevalence Of Human Brucellosis In Erbil Governorate Accordimentioning
confidence: 99%